Complex Shapes Are Bluish, Darker, and More Saturated; Shape-Color Correspondence in 3D Object Perception - Song, Jiwon; Shin, Haeji; Park, Minsun; Nam, Seungmin; Kim, Chai-Youn (Frontiers in Psychology, 2022)
It has been shown that there is a non-random association between shape and color. However, the results of previous studies on the shape-color correspondence did not converge. To address the issue, we focused on shape complexity among a number of shape properties, particularly in terms of 3D shape, and parametrically manipulated the shape complexity and all three components of color. With two experiments, the current study aimed to closely examine the correspondence between shape complexity of 3D shape and color in terms of hue (Experiment 1), luminance, and saturation (Experiment 2). Participants were presented with the 3D shapes in either visual or visuo-haptic modes of exploration. Subsequently, they had to pick from a color palette the color best matching each shape of the object. In Experiment 1, we found that as shapes became more complex, the best associated hue changed from those with long wavelengths to ones with short wavelengths. Results of Experiment 2 demonstrated that as the shapes grew more complex, the associated luminance decreased, and saturation increased. Additionally, adding haptic exploration to visual exploration strengthened the association, for saturation in particular, with the pattern of shape-color correspondence maintained. Taken together, we demonstrated that complex shapes are associated with bluish, darker and more saturated colors, suggesting that shape complexity has a systematic relationship with color including hue, luminance, and saturation.